2007
DOI: 10.1111/j.1600-0560.2006.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin and filaggrin expression in nevus comedonicus

Abstract: To elucidate the pathogenesis of abnormal keratinization in nevus comedonicus, we performed an immunohistochemical study using antikeratin and antifilaggrin (filament-aggregating protein) antibodies. There were no significant differences between nevus comedonicus and normal skin in cytokeratin expression. Although filaggrin was only detected in the granular layer in open comedones, filaggrin was detected in both superficial cells and also intermediate cells in closed comedones, suggesting that filaggrin is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…145 In fact, perifollicular fibrosis has been observed in lesions of nevus comedonicus. 68 Thus, indirect evidence supports the view that the Apert mutation of FGFR2 leads to infundibular overexpression of IL-1α, which appears to be the driving force of comedo formation in nevus comedonicus and Apert syndrome.…”
Section: Cross-talk Between Fgfr2 Egfr P63 and Lipogenesissupporting
confidence: 50%
See 3 more Smart Citations
“…145 In fact, perifollicular fibrosis has been observed in lesions of nevus comedonicus. 68 Thus, indirect evidence supports the view that the Apert mutation of FGFR2 leads to infundibular overexpression of IL-1α, which appears to be the driving force of comedo formation in nevus comedonicus and Apert syndrome.…”
Section: Cross-talk Between Fgfr2 Egfr P63 and Lipogenesissupporting
confidence: 50%
“…Unilateral acneiform nevus is considered to represent an extensive variant of nevus comedonicus. 68 The patient's general health status and that of his relatives did not show any abnormalities. Sequencing of the FGFR2 gene revealed a C to G mutation in the nevus which was not present in contralateral unaffected skin and in the DNA isolated from EDTA blood.…”
Section: Acneiform Nevus-nevus Comedonicusmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized that NC arises from a developmental defect in the mesodermal component of the pilosebaceous unit, wherein the resulting follicular structure is only able to produce soft keratin, which then accumulates [31]. One study found increased filaggrin expression in closed comedones of NC but found no differences in cytokeratin expression between NC and normal skin [36]. Further studies are needed to elucidate the role of keratin and filaggrin in the pathogenesis of NC.…”
Section: Nevus Comedonicusmentioning
confidence: 97%